New challenges in human monkeypox outside Africa: A review and case report from Italy - Mileto, Davide; Riva, Agostino; Cutrera, Miriam; Moschese, Davide; Mancon, Alessandro; Meroni, Luca; Giacomelli, Andrea; Bestetti, Giovanna; Rizzardini, Giuliano; Gismondo, Maria Rita; Antinori, Spinello (Travel medicine and infectious disease, 2022)
Human monkeypox (MPX) is a neglected zoonotic disease caused by the MPX virus a double-stranded DNA virus which belongs to the Poxviridae family genus Orthopoxvirus. It is endemic in the rural rainforests of Central and Western Africa where it is responsible of human sporadic cases and outbreaks since 1970. Outside Africa MPXV caused an outbreak in 2003 in the United States linked to importation of infected rodents from Ghana and a few travel-related cases in the USA, United Kingdom, Israel and Singapore. Actually, a worldwide outbreak with more than 1200 confirmed cases mainly concentrated among men who have sex with men is ongoing. We present the case of an Italian man living in Portugal that was diagnosed with MPX at our clinic in Milan, Italy. Monkeypox virus infection was confirmed by a specific homemade Real-Time PCR. Samples obtained from different sites (pharynx, skin lesions, anal ulcer, seminal fluid) turned all positive with different viral load. Our report illustrates the challenge of a disease that seems to present in a different way from classic description with possible human-to-human transmission through sexual contact.